Apple growing - Baird, Alfred Henry (My University, 1907)
Introduction: One of the fruits that has been cultivated from time immemorial is the apple. How to grow this most delicious fruit so that the best and largest yield might be obtained has been a subject of the greatest importance to the horticulturist. It is a subject of more interest today than every before. In this paper I will try to give a discussion of a few of the problems that confront the apple grower of today. Briefly stated they are: The treatment of the seedling, the planting of one or two year old apple trees, the training of the tree, and spraying for insects and fungus diseases.
Citation: Baird, Alfred Henry. Apple growing. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Apples; Planting Apples; Horticulture; Fruit; Issues in Horticulture; Theses